MODERN CONCEPTS OF THE CAUSES AND MECHANISMS OF DYSPEPSIA SYNDROME, THE ROLE OF ALLERGY IN THE DEVELOPMENT OF DYSPEPSIA - Mirsagatova Mavluda Rixsillayevna; Joʻrayeva Farogʻat Davron qizi; Uzbekov Shohjahon Shakarovich (Modern American Journals, 2025)
The relationship between gastrointestinal tract (GIT) lesions and allergic diseases is now widely recognized. Epidemiological studies have demonstrated a high frequency of their association, and the mechanisms underlying the development of allergies in gastrointestinal pathology have been largely elucidated. For example, the role of digestive disorders in sensitization and the development of allergies has been demonstrated [1]. Furthermore, the effects of biologically active substances that promote the development of allergic inflammation of the gastrointestinal mucosa are also known [5]. Atopic dermatitis (AD) is one of the most common allergic diseases in children, often accompanied by gastrointestinal lesions [7].